Crop productivity of wheat rotation systems for ten-year period, in Passo Fundo, RS, Brazil - Santos, Henrique Pereira dos; Ignaczak, João Carlos; Lhamby, Julio Cesar Barreneche (Pesquisa Agropecuaria Brasileira, 1995)
From 1980 to 1989, the effect of crop rotation systems for wheat was assessed at the Centro Nacional de Pesquisa de Trigo (CNPT), in Passo Fundo County, RS, Brazil. Four rotation systems for wheat were studied: system I (wheat/ soybean); system II (wheat/soybean, rapeseed/ soybean, barley/soybean, and white lupine or serradella/corn); system III (wheat/soybean, arrowleaf clover/arrowleaf clover, and arrowleaf clover/corn, from 1980 to 1983, and wheat/soybean, white oats/soybean, and common vetch/corn, from 1984 to 1989); and system IV (wheat/soybean, rapeseed/ soybean, flax/soybean, and white lupine or serradella/corn). A randomized complete block design, with four replications and plots with 120 m2, was used. Cultural productivity for that period, obtained by dividing grain yield (kg/ha) of each species by the energy consumed, is presented in this paper. The energy consumed is the energy spent to produce a good or a service. The global analysis showed no difference among systems I (1.20 kg/Mcal), II (1.42 kg/Mcal), III (1.45 kg/Mcal), and IV (1.40 kg/Mcal). In the annual average the alternative systems II, III and IV were five or more times higher than system I.